Natural Resource Management and Crop Production Strategies to Improve Regional Food Systems in Tanzania. (June 2015) - Graef, F.; Schneider, I.; Fasse, A.; Germer, J.U.; Gevorgyan, E.; Haule, F.; Hoffmann, H.; Kahimba, F.C.; Kashaga, L.; Kissoly, L.; Lambert, C.; Lana, M.; et al.
Sustainable rural food systems for poor and vulnerable people need to be locally adapted to enhance food security. This requires participatory action research that considers the entire food value chain (FVC). This paper presents an assessment of the feasibility and potential success of upgrading strategies (UPS) for enhancing food security based on a study that was part of a larger participatory research project in two regions of Tanzania. The authors present the results relating to natural resource management and crop production. The results for natural resources show that enhanced soil water management was rated as high for the semi-arid Dodoma region. For the Morogoro region, the experts favoured soil fertility-improving UPS, such as conservation agriculture and agroforestry. Assessments of food production for both regions indicated the importance of intercropping, manure input, pest and disease control and cover crops. Assessments differed greatly between the two different climatic regions, and to a lesser extent between the nationality of the experts and their gender. This highlights the importance of including different South–North and female–male awareness in assessments. Implementation feasibility assessments of UPS indicated that the most suitable approaches were rainwater harvesting for semi-arid and conservation agriculture for subhumid regions respectively. Local and/or regional stakeholders and experts should be involved in developing and assessing site-adapted UPS for enhancing Tanzanian FVCs.